ASSESSING ISLAMIC LEADERSHIP AND ITS EFFECT ON EMPLOYEE JOB SATISFACTION AT SME’S - Lila Bismala (Proceeding International Seminar of Islamic Studies, 2021)
Leadership and job satisfaction have an important role in improving company performance and productivity. Leadership with effective skills can help motivate employees and make them more satisfied with their working conditionsIslamic leadership is the focus of research because the research subjects are small and medium enterprises in the Muslim fashion sector, which want the implementation of Islamic leadership in their business management.Leaders who earn the trust of employees are easier to carry out their duties because employees trust their leadersThe dimensions of Islamic leadership used in this study include ihsan and noble morals, honesty, giving good role models, knowledge, trust, justice, patience, keeping words, deliberation, humble.Meanwhile, the dimensions of job satisfaction in this study include salary, rewards, relationships with colleagues, personal development, supervisors, work environment. The research subjects were employees of small businesses engaged in Muslim clothing, with a sample size of 100 employees.The results showed that there was a significant influence between Islamic leadership on employee job satisfaction.Key words: Islamic leadership, job satisfaction